THE ANALYSIS OF THE INFLUENCE OF MODIFICATION OF BOW DESIGN WITH AXE BOW TYPE ON TOTAL RESISTANCE ON 60 METER FAST MISSILE SHIPS - Kusdiana, Wawan; Ika, Aris Tri; Yudo, Valentinus; Rahman, Abdul; Syaifi, Mochammad (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2024)
The bow of the ship is an important part in the design of the ship, as is the bow of the KCR-60, because it is the part that experiences the greatest pressure, stress from the crashing waves, with the Axe Bow bow design which has a bow profile like an axe, the slender shape of the waterline is able to reduce impacts. waves, increase the efficiency of the inflow rate, reduce the resistance the ship receives, resulting in better speed. This research changes the Conventional Bow KCR-60 design into the Axe Bow design concept and calculates the total resistance of the Axe Bow design numerically using the Holtrop method and carries out comparative analysis using the MARIN DESPPC 1999 computing program and Maxsurf Resistance V8i software. The results of this research show that the total resistance value of the KCR-60 Axe Bow bow type at a speed of 28 Knots is 364.2 kN and the Conventional Bow type is 374.5 kN, a difference of 10.3 kN which is 2.75% smaller than the Conventional Bow type in the analysis. Maxsurf Resistance V8i software comparison. For comparative analysis of the 1999 MARIN DESPPC program, the total resistance value of the KCR-60 Axe Bow concept at a speed of 28 Knots is 283.6 kN and the Conventional Bow type is 288.1 kN, the difference is 4.5 kN, 1.56% smaller than the Conventional type Bow. Keywords: KCR-60, Axe Bow, MARIN DESPPC 1999, Holtrop.